Use of Global Positioning System in mine landscaping and visual impact assessment: A case study - Fadda, S.; Fiori, M.; Matzuzzi, C. (Journal of Nepal Geological Society, 2006)
The satellite-based Global Positioning System (GPS) needs a clear view of sky for determining a geodetic position and hence it is particularly suitable in overall projects of open-pit recovery and landscape restoration. The purpose of such measurements is to make highly accurate topographic maps thus forming the backbone of a project. In the work presented here geodetic measurements are combined with advanced visualisation techniques and GIS applications in a possible recovery plan of the abandoned excavations of Bonucoro in the mining district of Orani, central Sardinia, Italy. Considering the naturalistic and geographic settings of the mining area and its surroundings, a few proposals concerning the re-utilisation of these excavations are presented. The preparatory work consisted of the area characterisation by carrying out a topographic survey followed by a geodetic control network establishment by the GPS to describe the morphological features of the landscape and for the subsequent three-dimensional analysis and geoprocessing. The final step involved the use of VueInfinite, a computer program capable to integrate graphical data with geological and morphological attributes. It was also able to create a virtual 3D scene of a present, past, or future landscape required for visual impact assessment.